TRF2 recruits nucleolar protein TCOF1 to coordinate telomere transcription and replication - Nie, Xin (Cell Death Differ, 2020)
Telomeres are transcribed into telomeric RNA termed as TERRA. However, the transcription itself and excessive TERRA may interfere with telomere replication during S phase. The mechanism that coordinates telomere transcription and replication is unknown. Here, we report that TCOF1 leaves the nucleolus and is recruited to telomeres specifically during S phase by interacting with TRF2. Therein, TCOF1 acts to suppress telomere transcription by binding and inhibiting Pol II. Thus, TERRA is limited to low levels in S phase. Depletion of TCOF1 leads to abnormally elevated TERRA and formation of DNA/RNA hybrids (R-loops) at telomeres, which induces replication fork stalling and fragile telomeres. Importantly, telomere replication defect induced by TCOF1 deficiency can be rescued by either masking TERRA or expressing an R-loop eraser RNase H1, demonstrating a critical role of TCOF1 in coordinating telomere transcription and replication. These findings link nucleolus to telomeres and uncover a novel function of TCOF1 on ensuring telomere integrity.